Determinants of Gen-Z’s Decision to Use Islamic Banking Services in Malang City - Faqih, Ahmad Faqih Husaini; Aminullah, Aminullah Achmad Muttaqin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of Islamic financial literacy, trust, Islamic branding, service quality, and income on people's decisions to use Islamic banking services in Indonesia. With the rapid growth of the Islamic financial industry, a profound understanding of Islamic financial literacy is essential to attract a broader market share, particularly among the Muslim community. This research employs a quantitative approach with data collected through questionnaires distributed to respondents who utilize Islamic banking services. The data are analyzed using the Structural Equation Modeling with Partial Least Square (PLS-SEM) approach via SmartPLS 4 software. The results indicate that Islamic financial literacy, trust, Islamic branding, and service quality have a positive and significant effect on the decision to use Islamic banking services. These findings support the Theory of Planned Behavior, emphasizing the importance of attitude, subjective norms, and perceived behavioral control in decision-making. Conversely, income does not have a significant impact, suggesting that psychological and religious factors more dominantly influence consumers' decisions.